2018
DOI: 10.1634/theoncologist.2018-0346
|View full text |Cite
|
Sign up to set email alerts
|

Low Prevalence of the Four Common Colombian Founder Mutations in BRCA1 and BRCA2 in Early-Onset and Familial Afro-Colombian Patients with Breast Cancer

Abstract: Background Inherited mutations in the breast cancer susceptibility genes BRCA1 and BRCA2 (BRCA1/2) confer high risks of breast and ovarian cancer. In Colombian Hispanic families, four common BRCA1/2 founder mutations have previously been identified. Because nothing is known about the contribution of BRCA1/2 germline mutations to early‐onset and hereditary breast and/or ovarian cancer in Afro‐Colombians, we conducted the first study on 60 patients with early‐onset and familial breast cancer in this population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 19 publications
1
7
0
3
Order By: Relevance
“…Three patients had been diagnosed with BC before 35 years of age (5%); 48 belonged to families with at least 2 BC cases (80%) and 9 to families with both breast and OC (15%). The median ages of disease onset differed between BRCA1/2 carriers ( n = 5, including the previously identified BRCA1 _c.5123C>A carrier) 15 and noncarriers ( n = 55; 40 years, range 30-45 vs 51 years, range 33-70 years, P = .019 by Wilcoxon rank-sum test).…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…Three patients had been diagnosed with BC before 35 years of age (5%); 48 belonged to families with at least 2 BC cases (80%) and 9 to families with both breast and OC (15%). The median ages of disease onset differed between BRCA1/2 carriers ( n = 5, including the previously identified BRCA1 _c.5123C>A carrier) 15 and noncarriers ( n = 55; 40 years, range 30-45 vs 51 years, range 33-70 years, P = .019 by Wilcoxon rank-sum test).…”
Section: Resultsmentioning
confidence: 85%
“…All Afro-Colombian families affected by breast/OC who were investigated in this study have previously been described. 15 In summary, a total of 60 families comprising 51 affected by BC and 9 affected by both breast and OC were recruited at the Cancer Leagues in Cartagena, Quibdó, and San Andres Island, Colombia, from March to December 2016. Of the 60 index patients, 52 were Afro-Colombians and 8 were Raizales.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also cannot exclude that the mutation may have multiple ancestral origins in countries without a history of colonization by those countries, such as Canada or Norway, where this mutation has been also reported [ 7 , 33 ]. Furthermore, while our study in Colombia focused on communities from the central Andean region, where we have shown that they have a predominant European and Indigenous American ancestry [ 16 , 34 40 ], a recent study in Afro-Colombian populations from the west of the country also identified BRCA1 c.3331_3334delCAAG carriers, which may suggest additional origins in other Colombian groups [ 41 ]. A similar analysis with carriers from these populations would be necessary to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%